AUTONOMOUS LEARNING IN ELLE: CYBERNAUTICAL APPROACH AS THE VIADUCT TO L2 ACQUISITION - Jacob George C (Soegijapranata Catholic University, 2012)
Recent researches on cognitive methods show that institutionalized language learning is a constant source of stress, and a psychological obstacle leading to discomfort and insecurity. In the ELLE (Electronic Language Learning Environment) of the current times cybernautical approach opens attractive horizons by relaxing and empowering the learner, through its emphasis on communication, and by increasing interaction between the learner and the 'teacherfacilitator. This paper shows how the cybernautical approachfosters L2 acquisition by valorizing 'meaning' and 'content' over 'form' and 'competence in grammatical structures.' The attempt in the paper is to analyze the essential ingredients of the cybernautical approach and explore the practical content of the method in the context of the Sultanate of Oman. The focus of the presentation is on the (re)defining of the learning space-the classroomwhich has today become a major constraint owing to its spatial (fixed location) and temporal (fIXed class timetable) inflexibility.